Core self-evaluations and workplace deviance: The role of resources and self-regulation. Issue 5 (October 2015) - Neves, Pedro; Champion, Stephen
Abstract In this study, we examine the relationship between employees' core self-evaluations (CSE) and workplace deviance. Further, taking a person–environment perspective, we utilize a conservation of resources framework (Hobfoll, 1989), proposing that the degree to which employees are able to attain resources, versus the extent to which resources are drained from the individual, acts as a mediating mechanism between CSE and deviance. Specifically, we propose that employees' CSE is related to deviance through its association with a decrease in the depletion of resources (utilized as emotional exhaustion) and an increase in the ability to garner external resources by fostering social exchange relationships within the workplace (utilized as trust in the supervisor). Data were collected from 518 employee–supervisor dyads across 35 different organizations. Results revealed that trust in the supervisor fully mediated the relationship between CSE and deviance directed both at other individuals and the organization, while emotional exhaustion was a significant mediator for the relationship between CSE and interpersonal deviance. Implications for theory and practice are also discussed.